Reflection of Translation Strategies and Translation Norms in the Translation of Persian into English tourism-related websites - Sina Shams; Reza Gholami (Yayasan Visi Intan Permata, 2019)
The importance of tourism for the economies of the countries is indisputable. In line with this, websites introducing touristy landmarks as well as presenting general information as regards a country play an important role. It is well agreed that translating such websites would be a daunting task and evaluating them is then a need. To fulfil this, the current research was established to address in general the translation of Persian into English tourism-related websites. Toury’s Model was adopted to investigate the corpus of the study. The results proved that the most dominant strategy on the tourism related websites was omission, followed by manipulation of segmentation and euphemism. Also it was found that website translators used different strategies in transferring tourism words and sentences. The findings of this research showed that there are deficiencies in terms of norms and strategies. Further professional work is needed to boost the quality of the tourism related websites in the studied areas.